Assessment of chemical composition and microbiological properties of titanium nickelide supernatant - R. M. Uruzbaev (Scientific Сentre for Family Health and Human Reproduction Problems, 2018)
According to the World Health Organization, in the structure of internal injuries, burns occur in 2.1 per 1000 adults. In practice, all victims after stabilization of the condition are treated surgically with the autodermoplasty, which in the late period is accompanied by a rough scarring, sometimes with the deformation of the damaged area. In addition, infectious complications worsen and aggravate the wound healing process, and also significantly prolong the epithelialization time. A wound is usually infected by opportunistic pathogenic microflora resistant to various groups of antibiotics and antiseptics, by which the affected areas are treated. Modern researches are aimed at finding ways to accelerate regenerative processes of the affected area, to avoid surgical treatment and prevent infection contamination. The object of this study was titanium nickelide supernatant. Currently, there are no published data on the chemical composition of the supernatant, as well as its microbiological safety. This alloy is actively and successfully used in traumatology, dentistry and other fields of medicine. The supernatant was prepared under sterile conditions at a rate of 10 g of titanium nickelide powder per 1 liter of distilled water. In the course of the studies it was proved that nickel and titanium ions are present in the solution, in addition, its bactericidal and bacteriostatic properties are reflected. Thus, the supernatant of nitinol can be used in biological environment and is safe for them.